Immersive Virtual Reality Simulation in Forensic Psychiatry and Adjacent Clinical Fields: A Review of Current Assessment and Treatment Methods for Practitioners - Sygel, Kristina; Wallinius, Märta (Frontiers in Psychiatry, 2021)
Background Research has indicated that interactive, computerized case simulations using immersive virtual reality (VR) technology may be beneficial in the augmentation of conventional methods of assessment and treatment in forensic psychiatry, primarily through providing an engaging and safe environment in which the user can practice and learn skills and behaviours. However, there does not appear to be an overview of recent developments available in the field, which may be an obstacle to clinicians considering the use of VR in their clinical practice. Objectives New assessment and treatment methods applying immersive VR in forensic or adjacent clinical settings, which may be of use in clinical, forensic psychiatry, were explored. Methods This review surveyed the practical use of immersive VR in forensic psychiatry and relevant adjacent psychiatric and forensic fields from 2016 to 2020 and was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results Out of the 1105 journal articles screened, 14 met criteria for inclusion. Four articles described VR interventions directly addressing forensic psychiatric settings (treatment of general aggression and assessment of sexual offenders against children). The majority of the remaining articles were in the clinical domain of psychosis treatment. Several interventions were designed as part of comprehensive treatment programs, and others were intended as one-off assessments or paired with pre-existing psychological treatment. The degree to which the VR simulations were individualized to the user appeared to be largely dependent upon the extent of provider input. A variety of research methodologies were used in the included articles and the majority had limitations common to small-scale non-randomized studies. None of the studies reported serious adverse effects. Discussion There is a lack of large randomized controlled trials of assessments or treatments using VR simulation in forensic psychiatry, let alone those with long-term follow-up showing clear advantages of VR over standard practice. The evidence thus far is insufficient to recommend immediate and large-scale implementation of any one of the VR interventions included, however, several have been shown to be feasible and acceptable to the participants and to provide insights and inspiration for future research and development.